2021
DOI: 10.7759/cureus.14094
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuritis in a Child With COVID-19: A Rare Association

Abstract: The recent coronavirus disease-2019 (COVID-19) pandemic has caused significant mortality and morbidity, affecting patients of all ages. COVID-19 affects various tissues and systems in the body, including the central and peripheral nervous systems. However, COVID-19 has rarely affected the eyes and caused optic neuritis. We report a unique case of COVID-19-related unilateral optic neuritis in a 10-year-old girl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In a systematic review of case reports, AMAN was the least reported variant of GBS, occurring in 8 out of 77 cases [ 30 ]. To date, there are only two reports of pediatric optic neuritis associated with COVID-19, one occurring during active infection and one as the presenting symptom of MIS-C in a PCR-negative, seropositive child [ 32 , 33 ]. Patient 13 presented with acute vision impairment and neurophysiologic evidence of optic nerve demyelination in the face of a negative PCR and positive IgG.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of case reports, AMAN was the least reported variant of GBS, occurring in 8 out of 77 cases [ 30 ]. To date, there are only two reports of pediatric optic neuritis associated with COVID-19, one occurring during active infection and one as the presenting symptom of MIS-C in a PCR-negative, seropositive child [ 32 , 33 ]. Patient 13 presented with acute vision impairment and neurophysiologic evidence of optic nerve demyelination in the face of a negative PCR and positive IgG.…”
Section: Discussionmentioning
confidence: 99%
“…Vasculitis may accompany intracranial infections and up to one-third of children with stroke have postvaricella angiopathy occurring weeks to months after uncomplicated chickenpox [ 94 ]. Vasculitis and associated infarction are frequent reported in children with COVID-19 infection [ 10 , 20 , 21 , [41] , [42] , [43] , [44] , [45] , [46] , [47] ].…”
Section: Mr Neuroimagingmentioning
confidence: 99%
“…[ 10 ]. Numerous case reports have indicated the presence of acute encephalopathy or encephalitis [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], acute necrotizing encephalopathy (ANE) [ 25 , 26 ], acute disseminated encephalomyelitis (ADEM) [ 20 , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], cytotoxic lesions in the callosal splenium [ 26 , [33] , [34] , [35] , [36] , [37] ], posterior reversible encephalopathy syndrome (PRES) [ 26 , 38 ], cerebral venous thrombosis [ 39 , 40 ], vasculitis and acute infarction [ 20 , 21 , [41] , [42] , [43] , [44] , [45] , [46] , [47] ], Guillain–BarrĂ© syndrome (GBS) [ 20 , 21 , 26 , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ] and its variant Miller-Fisher syndrome (MFS) [ [59] , [60] , [61] , [62] ], transverse myelitis [ 9 , 50 ,…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of left optic neuritis was then confirmed by the orbit's MRI, which showed moderate enlargement and minor T2 hyperintensity of the left optic nerve's intracanalicular and intraorbital segments. 50 …”
Section: Complications In Paediatric Populationmentioning
confidence: 99%